(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The RA frontier settlements are primarily villages and among the other factors, their perspective development depends on the population number of settlements and age structure of population as well. Based on the analysis and generalization of factual and statistical data, the regional differences of the rural population age structure of the RA frontier areas are given in the article. The current problems have been revealed.